Clinical Updates on Birt-Hogg-Dubé Syndrome and Atypical Presentations: Diagnosis and Management - Brown, Madeline; Hwang, Jacqueline; Khachemoune, Amor (Dermatology Practical & Conceptual, 2026)
Introduction: Birt-Hogg-Dubé (BHD) syndrome is a rare hereditary genodermatosis associated with a mutation in the folliculin (FLCN) gene. Diagnostic criteria for this disease were first established in 2009. Objectives: This review aimed to reassess current guidelines by taking into consideration incomplete forms of the syndrome, as patients may present clinical features of BHD without a detectable FLCN gene mutation. Methods: Recent findings of new germline mutations and associated phenotypes were analyzed to evaluate the adequacy of existing diagnostic criteria. Results: Researchers have come across novel germline mutations and phenotypes, revealing that some individuals with features of BHD may not carry the FLCN mutation. These findings suggest the existence of incomplete or atypical presentations of the syndrome. Conclusions: Individuals who share any characteristics of BHD should be screened, as patient outcomes depend heavily on early detection. Updated diagnostic approaches are needed to account for the broader phenotypic spectrum of the disease.